(3GdcfGT GdeTLQ GdcHjQs - (3CHh RcQjGA jhMfG Hf eGShjI GdHZOGOj,J (B243 (3g` s ((3CHh GdeXaQ Hf Ydi Hf CHj GdaJM GdbQTi GdeJWHH s)
(3ChdgG (B:s
(3cfGT Ydd GdCeQGV hOdGFdgG hYdGLGJgG , hgh GdcfGT GdeYQha HGdeTLQ GdcHjQ GdHGH GdChd OGA GdKYdH Cf OGA GdKYdH jJchf ef GeGef GdeQI hGdUaQGA s
(3BNQgG (B:s
(3jOb hjfNd hHYLf HeGA GdcQaS hjbQU , hjSbi efg HGdScfLHjf s
(3hHBNQ GdfSNI aUd fbdg GdfGSN Yf GdCUd jajO Cf GdcJGH JQcg GHf eGShjg HGdSQjGfjI hJQLeg Edi GdYQHjI OGfjGd ? HWdH efUhQ Hf WdMg ehdi CejQ GdeDefjffs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B158 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs